From disorder of tonic dialogue to psychomotor instability: Diagnostic taxonomy - Boscaini, Franco; Cachón Zagalaz, Javier; Díaz Suárez, Arturo (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The goal of this work is to deepen the relationship between hyperactivity and tonic dialogue, by considering the body as a common element of communication even if their psychomotor manifestations and meanings are different during development. While tonic dialogue is vital for the child in the constitution of the attachment bond, psychomotor instability is the expression of a difficulty in relating to reality. In the clinic it is difficult to place instability in international diagnostic classifications, due to the multi-problematic nature and variability of expressions of it. Research confirms the consequences of a disorder of tonic dialogue, constituting a model on which future behaviors will be organized. The authors hypothesize that each stage of the body communication, if lived with difficulty, constitutes a matrix on which diversified expressions of instability will be structured. The intent, therefore, is to collect theoretical-clinical material in order to subsequently make a diagnostic classification of psychomotor instability.